Feasibility study of real‐time planning for stereotactic radiosurgery. Issue 3 (26th February 2013) - Zhang, Qinghui; Song, Yulin; Chan, Maria; Burman, Chandra; Yamada, Yoshiya
Abstract : Purpose: : 3D rotational setup errors in radiotherapy are often ignored by most clinics due to inability to correct or simulate them accurately and efficiently. There are two types of rotation‐related problems in a clinical setting. One is to assess the affected dose distribution in real‐time if correction is not applied and the other one is to correct the rotational setup errors prior to the initiation of the treatment. Here, the authors present the analytical solutions to both problems. Methods: : (1) To assess the real‐ time dose distribution, eight stereotactic radiosurgery (SRS) cases were used as examples. For each plan, two new sets of beams with different table, gantry, and collimator angles were given in analytical forms as a function of patient rotational errors. The new beams simulate the rotational effects of the patient during the treatment setup. By using one arbitrary set of beams, SRS plans were recomputed with a series of different combinations of patient rotational errors, ranging from (−5°, −5°, −5°) to (5°, 5°, 5°) (roll, pitch, and yaw) with an increment of 1° and compared with those without rotational errors. For each set of rotational errors, its corresponding equivalent beams were computed using the analytical solutions and then used for dose calculation. (2) To correct for the rotational errors, two new sets of table, gantry, and collimator angles were derived analytically to validate the previously published derivation. However, in the derivation, a novel methodology was developed and two sets of table, gantry, and collimator angles were obtained in analytical forms. The solutions provide an alternative approach to rotational error correction by rotating the couch, gantry, and collimator rather than the patient. Results: : For demonstration purpose, the above‐derived new beams were implemented in a treatment planning system (TPS) to study the rotational effects on the SRS cases. For each case, the authors have generated ten additional plans that accounted for different rotations of the patient. They have found that rotations have an insignificant effect on the minimal, maximum, mean doses, and V 80% of the planning target volume (PTV) when the rotations were relatively small. This was particularly true for the small and near‐spherical targets. They, however, did change V 95% significantly when the rotations approached 5°. The theory has been validated with clinical SRS cases and proven to be practical and viable. The preliminary results demonstrate that the rotational effects are patient‐specific and depend on several important factors, such as the PTV size, the PTV location, and the beam configuration. The solutions given in this paper are of great potential values in clinical applications. Conclusions: : They have derived the analytical solutions to a new set of table, gantry, and collimator angles for a given treatment beam configuration as a function of patient rotational errors. One solution was used to assess the dosimetric effects of an imperfect patient setup and the other one was used to correct for the setup errors without rotating the patient. Compared to the widely adopted method of rotation effect assessment by importing the rotational CT images into TPS, the equivalent beam approach is simple and accurate. The analytical solutions to correcting for rotational setup errors prior to treatment were also derived. Based on the initial clinical investigations, they firmly believe that clinically viable real‐time treatment planning and adaptive radiation therapy are feasible with this novel method.